(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article highlights the role of folklore in its interaction with piano music, which covers a wide aspect in the activities of professional musicians. And also participates in the education of children’s and youthful creativity, cultivating numerous talents on this basis.